AN INTERPRETATIVE PHENOMENOLOGICAL ANALYSIS ON THE CONCEPT OF FAMILY AMONG ABANDONED YOUNG ADULTS WITH PHYSICAL DISABILITY - Ampong, Yoldy Ann; Delos Santos, Crystal Jade; Tolosa, Mary Jessica (PEOPLE: International Journal of Social Sciences, 2018)
Most people who live with physical disability belong to the poorest and marginalized. In familial context, being a young adult with physical disability sets extra demand towards the family because it causes exhaustion due to the additional care, attention and maintenance for medication. As a response to this, families seek the help of institutions with the belief that the individual with physical disability could get necessary help through them. It was due to those that the possibility of abandonment increases. The study utilized interpretative phenomenological analysis to explore the concept of family among abandoned young adults with physical disability as a response to the aforementioned issues. Derived from these were the objectives of this study:[1] To know their view towards each member of the family and [2] to know how the abandonment affected their concept of family. Participants include 3 abandoned young adults with apparent physical disabilities (e.g. cerebral palsy, kyphosis and hip dysplasia) which are all from the province of Cavite, Philippines. Interview and drawing were the methods used to elicit responses. Results show that before abandonment, 1 superordinate theme emerged: primary family as an attachment unit; and for after abandonment, another superordinate theme emerged: Alternate family as a unit of healing and recovery. These were supported by local and international research and theories regarding topics that tackle the importance of the alternate family and the faith and values accumulated as ways to reconstruct the self, as well as the young adults’ aspirations to be reunited with their family amidst abandonment.